ANALYSIS OF PUBLIC PERCEPTION OF THE QUALITY AND ACCESS TO CLEAN WATER IN SEI RAJA SUBDISTRICT, TANJUNG BALAI CITY - Yoppie Prayoga S; Cut Nuraini; Abdi Sugiarto (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze public perceptions of the quality and accessibility of clean water services in Sei Raja Village, Tanjungbalai City. The approach used is a qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. The results of the study indicate that most people still complain about the condition of clean water used daily. The main problems felt by the community are the quality of water which is still colored, smelly, and tasteless, as well as the unequal access to clean water services, especially in areas far from the main distribution network. In addition, technical constraints such as limited infrastructure, distance to water sources, and service capacity also affect public satisfaction. The community has high hopes for the improvement of clean water services, both in terms of quality and distribution reach, as well as the active involvement of the government and community in participatory water management.